Detection of plasmid-mediated qnr genes among the quinolone-resistant Escherichia coli isolates in Iran - Farzaneh Firoozeh; Mohammad Zibaei; Younes Soleimani-Asl (Journal of Infection in Developing Countries)
Introduction: Plasmid-mediated quinolone resistance, which complicates treatment, has been increasingly identified in Escherichia coli isolates worldwide. The purpose of this study was to identify the plasmid-mediated qnrA and qnrB genes among the quinolone-resistant Escherichia coli isolated from urinary tract infections in Iran. Methodology: A total of 140 Escherichia coli isolates were collected between March and October 2012 from urinary tract infections in Khorram Abad, Iran. All isolates were tested for quinoloe resistance using the disk diffusion method. Also, all quinolone-resistant isolates were screened for the presence of the qnrA and qnrB genes by polymerase chain reaction. Minimum inhibitory concentrations (MICs) of ciprofloxacin for the qnr-positive isolates were determined. Results: One hundred sixteen (82.8%) of 140 Escherichia coli isolates were nalidixic acid-resistant; among them, 14 (12.1%) and 9 (7.8%) were qnrA and qnrB-positive, respectively. Two quinolone-resistant isolates harbored both qnrA and qnrB. Among 63 ciprofloxacin-resistant isolates, 14 (22.2%) and 9 (14.3%) were found to carry qnrA and qnrB genes, respectively. The ciprofloxacin MIC range was 0.25–512 μg/mL for 23 qnr-positive Escherichia coli isolates, 18 of which had MICs values of 4–512 μg/mL. Conclusion: Our study shows that the frequency of plasmid-mediated quinolone resistance genes among E. coli isolates in Iran is high.